1998
DOI: 10.1046/j.1523-1747.1998.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Cytokines in Chronic Oxazolone-Induced Contact Sensitivity Suggest Roles for Tumor Necrosis Factor α and Interleukin-4

Abstract: An analysis was conducted of the cytokine profile and inflammatory response in oxazolone sensitized mouse skin. Following exposure to oxazolone, the intralesional production of inflammatory cytokines was demonstrable at the levels of both mRNA and protein. An initial challenge led to a transient increase in tumor necrosis factor-alpha production followed predominately by the T helper (Th)1 cytokine, interferon-gamma. There was a minimal production of interleukin-4, a Th2 cytokine. Continued exposure to oxazolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 20 publications
5
81
0
Order By: Relevance
“…2 These highlight the importance of lymph flow, which delivers antigen to the lymph node, to adaptive immunity. Whereas increased levels of cytokine production is observed from 4 hours, peaking at 16 hours after challenge in a skin lesion model, 39 increased interstitial flow is an immediate response to certain types of peripheral inflammation. 6 Our data show that both fluid and cell transport are enhanced on increased flow, and because flow can increase immediately, it is likely to be an important mediator of early responses to inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…2 These highlight the importance of lymph flow, which delivers antigen to the lymph node, to adaptive immunity. Whereas increased levels of cytokine production is observed from 4 hours, peaking at 16 hours after challenge in a skin lesion model, 39 increased interstitial flow is an immediate response to certain types of peripheral inflammation. 6 Our data show that both fluid and cell transport are enhanced on increased flow, and because flow can increase immediately, it is likely to be an important mediator of early responses to inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…While the reaction to oxazolone is predominantly a Th1-dependent response in which both TNF-a and IFN-c have been shown to play a role, multiple other cytokines such as IL-4, IL-10 and IL-6 have also been shown to participate in this response [26,[35][36][37][38]. Previous studies have suggested that TNF-a is the main inflammatory cytokine, as blockade of TNF-a prevented the CS response, while IFN-c blockade only had a partial protective effect [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TNF-a is present in the skin very early after challenge, with peak levels seen 4 h post-hapten challenge [26]. IFN-c levels are also increased significantly by 4 h with peak levels observed at 12-16 h post-hapten challenge [26]. Given the different time profiles of cytokine expression, the early, intermediate and late phases of the CS response were examined.…”
Section: No Can Down-regulate Lymphocyte Recruitment During the Elicimentioning
confidence: 99%
“…IgE-triggered release of mediators by dermal mast cells is responsible for onset of the edema response that occurs 30 min after elicitation (9,13). Therefore, serum total IgE levels were assessed on days 0, 7, 14, and 24 of Ag challenge.…”
Section: Adhesion Molecule Deficiency Suppressed Serum Ige Levelsmentioning
confidence: 99%